ISOLASI, SELEKSI, DAN KARAKTERISASI MIKROBA PENDEGRADASI ASETONITRIL DARI LIMBAH INDUSTRI - Sunarko, Bambang; Adityarini, Adityarini; Tambunan, Usman Sumo F; Sulistinah, Nunik (Research Center for Biology-Indonesian Institute of Sciences, 2000)
A number of microbes which could grow on acetonitrile were isolated and selected from industrial effluents and were studied to characterise the isolate which has the best degrading capability.Cultures were grown on mineral medium with microelements and acetonitrile was added as sole source of energy, carbon, and nitrogen.Isolate D5, identified as Corynebacteriumsp.,was able to grow on high concentration acetonitrile (up to 5 % v/v) and exhibited the highest specific growth rate (j).When Corynebacterium D5 grew on 2 % (v/v) acetonitrile,the doubling time was 6 hours 40 minutes,the specific growth rate (p) was 0.1 h and the acetonitrile decreasing rate was 3.99 mM/h.Increasing of acetonitrile concentration would extend the doubling time, decline the maximum growth and specific growth rate (i), and biomass production of Corynebacterium 05.The products of acetonitrile degradation by Corynebacterium D5 were acetamide, acetic acid, and ammonia.The maximum growth of Corynebacterium D5 showed when /3-aminopropionitrile was used as a substrate.